An axiomatization of the sequential Raiffa solution - Walter Trockel (Bielefeld University, Institute of Mathematical Economics (IMW), 2009)
This paper provides four axioms that uniquely characterize the sequential Raiffa solution proposed by Raiffa (1951, 1953) for two-person bargaining games. Three of these axioms are standard and are shared by several popular bargaining solutions. They suffice to characterize these solutions on TU-bargaining games where they coincide. The fourth axiom is a weakening of Kalai's (1977) axiom of step-by-step negotiating and turns out to be sort of a dual condition to a weaker version of Nash's IIA-axiom that together with the three standard axioms suffices to characterize the Nash bargaining solution due to Nash (1950). A conclusion of this axiomatization is that in contrast to all other known bargaining solutions the sequential Raiffa solution does not represent just another kind of fairness or equity condition in addition to the three standard axioms but rather is determined by indefinite repeated application of the three standard axioms.
urn:nbn:de:hbz:361-16196
Keywords: 330; Bargaining games; Raiffa solution; Nash solution; Axiomatization; Verhandlungstheorie; Nash-Gleichgewicht; Theorie